ANALISIS RESIKO DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA GULA SEMUT ORGANIK - Yusuf Enril Enril Fathurrohman; Pujiati Utami; Alfato Yusnar Kharismasyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
This research aims to determine the factors that influence the production of ant sugar, and the risks of the ant sugar business in the Sumber Rejeki Joint Business Group (KUB) in Purbalingga Regency. The method used is a quantitative descriptive method with a sample size of 50 sap palm farmers. Regression analysis and risk analysis using the coefficient of variation are used to answer the objectives of this research. The results of this research show that the number of trees, cost, and land area have a significant effect on ant sugar production. The length of business and age do not have a significant effect. The results of the risk analysis show that relatively small risks include cost and production risks with a Coefficient of Variation (CV) of less than 0.5, even price risk, even though L > 0, has a CV = 0, which means the break-even point. Meanwhile, Income Risk is classified as high because it is above 0.5 and has a lower value of less than 0.